Recent Advances in Nonstationary Time Series: A Festschrift in honor of Peter C. B. Phillips - MARIANO, Robert S. (Institutional Knowledge at Singapore Management University, 2012)
On July 14–15, 2008, the School of Economics and the Sim Kee Boon Institute for Financial Economics at Singapore Management University (SMU) co-hosted a conference honoring the contribution of Peter Phillips to econometrics and statistics, in celebration of his 60th birthday. In total, 51 papers were presented by his colleagues and former students, who deeply appreciate and respect Peter as a true scholar and a good friend. These papers mainly cover two areas of Peter’s current research interests—nonstationary time series analysis, and panel, nonlinear and nonparametric models. On the basis of this conference, we have taken the opportunity to edit two special issues of the Journal of Econometrics (JoE), focused on these two research areas, to honor Peter Phillips on his 60th birthday. All papers in the two issues were selected from the SMU conference presentations and subjected to JoE’s normal refereeing process. This special issue contains 16 papers dealing with nonstationary time series analysis.